A frozen Christmas [videorecording (DVD)] (Ruthless, 2016)
Perfect way to get the family in the Holiday spirit. Includes the most beloved animated Christmas characters such as Santa Claus, Reindeer, and Elves. Santa and his elves narrate these Christmas classics.